Empirical compensation of reciprocity failure and integration time nonlinearity in a mid-wave infrared camera. (29th December 2015) - Romm, I; Lev, M; Cukurel, B
Abstract: Thermal-infrared radiation measurements, conducted using an InSb camera, indicated a failure of the reciprocity law for a wide range of radiation intensities and integration times. When reciprocity between radiation flux and integration time was assumed, the radiation estimates, computed from different combinations of output signals and selected integration time values, suffered from imprecisions of up to 12%. Temperature errors of 4% were predicted for low emissivity surfaces, at all temperatures. A novel empirical methodology, which compensates for multiple nonlinearity effects, is presented. Among different types of models, it is demonstrated that an equation, which represents a power-law dependence of the output signal on integration time best describes the physical system. Experimental procedures are suggested to avoid nonlinearity-related errors.